At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To find the value of [tex]\( n \)[/tex] given the equations [tex]\(\sqrt[3]{y^2} = \sqrt[6]{x}\)[/tex] and [tex]\( y = \sqrt[n]{x} \)[/tex], we will solve the system step-by-step.
### Step 1: Rewrite the first equation
The first equation is:
[tex]\[ \sqrt[3]{y^2} = \sqrt[6]{x} \][/tex]
This can be rewritten using exponents:
[tex]\[ (y^2)^{1/3} = x^{1/6} \][/tex]
Simplify the left side:
[tex]\[ y^{2/3} = x^{1/6} \][/tex]
### Step 2: Rewrite the second equation
The second equation is:
[tex]\[ y = \sqrt[n]{x} \][/tex]
This can also be rewritten using exponents:
[tex]\[ y = x^{1/n} \][/tex]
### Step 3: Substitute [tex]\( y \)[/tex] in the first equation
Substitute [tex]\( y = x^{1/n} \)[/tex] into the first equation [tex]\( y^{2/3} = x^{1/6} \)[/tex]:
[tex]\[ (x^{1/n})^{2/3} = x^{1/6} \][/tex]
Simplify the left side by multiplying the exponents:
[tex]\[ x^{(1/n) \cdot (2/3)} = x^{1/6} \][/tex]
This results in:
[tex]\[ x^{2/(3n)} = x^{1/6} \][/tex]
### Step 4: Equate the exponents
Since the bases are the same, the exponents must be equal:
[tex]\[ \frac{2}{3n} = \frac{1}{6} \][/tex]
### Step 5: Solve for [tex]\( n \)[/tex]
To solve for [tex]\( n \)[/tex], cross-multiply:
[tex]\[ 2 \cdot 6 = 1 \cdot 3n \][/tex]
Simplify:
[tex]\[ 12 = 3n \][/tex]
Divide both sides by 3:
[tex]\[ n = \frac{12}{3} \][/tex]
[tex]\[ n = 4 \][/tex]
### Conclusion
The value of [tex]\( n \)[/tex] is:
[tex]\[ \boxed{4} \][/tex]
### Step 1: Rewrite the first equation
The first equation is:
[tex]\[ \sqrt[3]{y^2} = \sqrt[6]{x} \][/tex]
This can be rewritten using exponents:
[tex]\[ (y^2)^{1/3} = x^{1/6} \][/tex]
Simplify the left side:
[tex]\[ y^{2/3} = x^{1/6} \][/tex]
### Step 2: Rewrite the second equation
The second equation is:
[tex]\[ y = \sqrt[n]{x} \][/tex]
This can also be rewritten using exponents:
[tex]\[ y = x^{1/n} \][/tex]
### Step 3: Substitute [tex]\( y \)[/tex] in the first equation
Substitute [tex]\( y = x^{1/n} \)[/tex] into the first equation [tex]\( y^{2/3} = x^{1/6} \)[/tex]:
[tex]\[ (x^{1/n})^{2/3} = x^{1/6} \][/tex]
Simplify the left side by multiplying the exponents:
[tex]\[ x^{(1/n) \cdot (2/3)} = x^{1/6} \][/tex]
This results in:
[tex]\[ x^{2/(3n)} = x^{1/6} \][/tex]
### Step 4: Equate the exponents
Since the bases are the same, the exponents must be equal:
[tex]\[ \frac{2}{3n} = \frac{1}{6} \][/tex]
### Step 5: Solve for [tex]\( n \)[/tex]
To solve for [tex]\( n \)[/tex], cross-multiply:
[tex]\[ 2 \cdot 6 = 1 \cdot 3n \][/tex]
Simplify:
[tex]\[ 12 = 3n \][/tex]
Divide both sides by 3:
[tex]\[ n = \frac{12}{3} \][/tex]
[tex]\[ n = 4 \][/tex]
### Conclusion
The value of [tex]\( n \)[/tex] is:
[tex]\[ \boxed{4} \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.